Integration of Ethnoscience in Module Based 3D Page Flip Technology: Innovation Learning for Increase Creative Thinking Skill - Nursamsu; Ekariana S. Pandia; Asmaul Husna; Ernawati (Postgraduate, University of Mataram, 2025)
This study aims to develop a medicinal plant module using 3D Page Flip technology integrated with ethnoscience to enhance students' creative thinking skills. The integration of ethnoscience connects scientific concepts with local wisdom, making learning more contextual, meaningful, and relevant to students' daily lives. The research follows the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The limited trial involved junior high school students familiar with local scientific knowledge. Instruments used included expert validation sheets, student response questionnaires, and creative thinking skill tests. The developed module was found to be highly valid, with a feasibility score of 87.5%. Its practicality was rated very high, based on teacher responses (84.40%) and student responses (87.52%). The results also showed a significant improvement in students' creative thinking skills after using the module. Therefore, the ethnoscience-integrated 3D Page Flip module is effective as a practical guide and learning media in biology to support the development of creative thinking skills.